EVALUASI STATUS KESUBURAN TANAH DI DESA PARBALOHAN KECAMATAN SIMANINDO KABUPATEN SAMOSIR - Sianipar, Ebsan Marihot; Sihombing, Parsaoran; Hulu, Ferdianus (Universitas Methodist Indonesia, 2023)
Soil fertility is a determining factor for plant growth and production. For this reason, it is important to evaluate the status of soil fertility as a basis for soil management. This study aims to determine the status of soil fertility by analyzing the nutrient content found in the soil in Parbalohan Village, Simanindo District, Samosir Regency. Survey and soil analysis methods are used to evaluate soil fertility status. Soil sampling is carried out for each land map unit (SPL) that has been determined from the mapping results. Principal component analysis to identify soil fertility consists of five main components including cation exchange capacity (CEC), base saturation (KB), C-organic content, P-total and K-total based on the criteria of the Bogor Soil Research Center (PPT) 1995. Results research shows that the status of soil fertility in Parbalohan Village, Simanindo District, Samosir Regency is low soil fertility. Limiting factors include soil reactions, acid pH and low KB can be corrected by adding calcite or dolomite lime. Soils with limiting factors for C-organic content and CEC can be improved by adding soil organic matter, manure and compost.